Unveiling the gut’s plastic predicament: How micro- and nano-plastics drive distinct toxicological pathways in Enchytraeus crypticus - Xing Li; Hao Qiu; Wenxing Li; Cornelis A.M. Van Gestel; Chao Jin; Erkai He (Environment International, 2025)
The gut microenvironment is crucial for maintaining health of its host. However, there is currently limited mechanistic understanding of how stress from microplastics (MPs) and nanoplastics (NPs) alter this environment and its resulting biotoxicity. Here, we systematically investigated the biological responses — from physiology to pathology and from molecular interactions to phenotypic changes — of the soil invertebrate Enchytraeus crypticus exposed to environmentally relevant concentrations of polystyrene MPs (50 μm) and NPs (100 nm). Exposure in a simulated soil matrix spiked with MPs and NPs differently reshaped the gut microenvironment of the worms due to their distinct gastrointestinal fate, thereby inducing different adverse effects via distinct molecular signaling pathways. The high bioaccumulation potential and prolonged retention of NPs in the gut facilitated their interaction with the gut interface, leading to gut acidification and an overaccumulation of H2O2 in gut. As a signal molecule, excessive H2O2 activated the TNF signaling pathway, which subsequently perturbed membrane-associated lipid metabolism and compromised gut barrier integrity through apoptosis. Unlike NPs, MP accumulation in the gut stimulated mucus secretion as a protective mechanism against physical damage, but disrupted fat digestion and absorption pathways, ultimately inducing cell aging through cardiolipin-mediated mitochondrial dysfunction alongside abnormal lipid droplet accumulation. Collectively, our findings provide mechanistic insights into the different biological and molecular responses to MPs and NPs within the context of an altered enchytraeid gut microenvironment.